2019
DOI: 10.20448/2002.72.82.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra Group Transaction, Thin Capitalization and Executive Characters on Tax Avoidation with Multinationality as a Moderation

Abstract: The purpose of this study is to examine the factors of tax avoidance in business groups / corporate groups in Indonesia, especially those belonging to the property sector which is listed on the Indonesia Stock Exchange (IDX) using variables such as intragroup transaction, thin capitalization, executive character and multinationality and firm size, profitability, intangible assets and debts as control variables. In this research, the object taken is secondary data, namely the financial statements of business gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The result of this test confirms the result of Taylor and Richardson (2012) using public company data in Australia, Falbo, and Firmansyah (2018), as well as Pratiwi and Ratnasari (2019), which tested at manufacturing companies in Indonesia. However, the result of this study is not in line with the testing of Ismi and Linda (2018), Salwah and Herianti (2019), Andawiyah et al (2019), and Bandiyono and Murwaningsari (2019). Differences in research results can occur due to differences in the companies' samples.…”
Section: The Effect Of Thin Capitalization On Tax Avoidancecontrasting
confidence: 91%
See 1 more Smart Citation
“…The result of this test confirms the result of Taylor and Richardson (2012) using public company data in Australia, Falbo, and Firmansyah (2018), as well as Pratiwi and Ratnasari (2019), which tested at manufacturing companies in Indonesia. However, the result of this study is not in line with the testing of Ismi and Linda (2018), Salwah and Herianti (2019), Andawiyah et al (2019), and Bandiyono and Murwaningsari (2019). Differences in research results can occur due to differences in the companies' samples.…”
Section: The Effect Of Thin Capitalization On Tax Avoidancecontrasting
confidence: 91%
“…In Indonesia, Falbo and Firmansyah (2018) researched manufacturing companies referring to the size of Taylor and Richardson (2012) with the provisions of Indonesian taxation and obtained the results that thin capitalization positively affects tax avoidance. Bandiyono and Murwaningsari (2019), who used property company data, and Prastiwi and Ratnasari (2019), using data from manufacturing companies in Indonesia, proved that thin capitalization positively affects tax avoidance. Previous research has shown that companies can use thin capitalization to avoid tax avoidance by increasing debt composition in their capital structure.…”
Section: Transfermentioning
confidence: 99%
“…This is in line with the mandate of Law Number 25 the Year 2009 regarding Public Services and in the context of increasing DGT performance achievements. One effort to achieve a high level of satisfaction with taxation services is to improve the quality of services to taxpayers (Bandiyono, A., & Murwaningsari, 2019). To improve the quality of service to taxpayers to create excellent service, it is necessary to build a service mindset as part of the application of the Ministry of Finance's values of professionalism and service in all DGT levels .…”
Section: Excellent Service According To the Director-general Of Tax Circular Number Se -84 / Pj / 2011mentioning
confidence: 99%
“…Agency Theory. According to (Bandiyono and Murwaningsari, 2019), agency theory is based on the existence of agency relationships. An agency relationship is a contract in which one or more owners of economic resources (principles) involve other parties (agents) to manage these resources on behalf of the principal.…”
Section: Theoretical Reviewmentioning
confidence: 99%